BAGAIMANA PRESTASI KERJA DIPENGARUHI DISIPLIN KREATIFITAS DAN TANGGUNG JAWAB DI SEKTOR KONTRUKSI - Adjie, Kemal Setia; Supriyadi, Andhi; Guritno, Bambang; Supriyanto, Sapto (ITB AAS Indonesia Surakarta, 2024)
Discipline, creativity and responsibility influence employee work performance. The aim of this research is to analyze discipline, creativity and responsibility whose impact on work performance is both partial and simultaneous. Type of explanatory research or level of explanation using census research techniques. Discipline, creativity, and responsibility are the independent variables of this research. This research refers to the entire staff of 134 road construction contractors. Validity and reliability tests, coefficient of determination, t test, and F test were carried out using SPSS calculation tools. The anova test shows that the model is fit, meaning that the independent variables can predict the dependent variable. The results show that all hypotheses are accepted. Research finds that discipline, creativity and responsibility have a significant impact on employee work performance, either partially or simultaneously. The results show that all hypotheses are accepted. Keywords: discipline, creativity, responsibility, work perfomance